2016
DOI: 10.3390/genes7120122
|View full text |Cite
|
Sign up to set email alerts
|

Host-Derived Artificial MicroRNA as an Alternative Method to Improve Soybean Resistance to Soybean Cyst Nematode

Abstract: The soybean cyst nematode (SCN), Heterodera glycines, is one of the most important pests limiting soybean production worldwide. Novel approaches to managing this pest have focused on gene silencing of target nematode sequences using RNA interference (RNAi). With the discovery of endogenous microRNAs as a mode of gene regulation in plants, artificial microRNA (amiRNA) methods have become an alternative method for gene silencing, with the advantage that they can lead to more specific silencing of target genes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…Wheat Stem Sawfly larva accommodates in wheat stem and feeds from there until pupae stage of its life cycle ( Delaney et al, 2010 ). Given the evidence of cross-kingdom regulation by miRNAs ( Zhang et al, 2012 ; Tian et al, 2016 ; Jia et al, 2017 ), the interaction between intracellular molecules of WSS larvae and wheat cannot be underestimated due to these two organisms being in contact and trying to defeat each other. To assess possible effects of larval miRNAs on wheat gene expression and its response to WSS pathogen, target analysis for larval miRNAs was performed against Triticum aestivum coding sequences deposited at ensemble plant database using psRNAtarget tool.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wheat Stem Sawfly larva accommodates in wheat stem and feeds from there until pupae stage of its life cycle ( Delaney et al, 2010 ). Given the evidence of cross-kingdom regulation by miRNAs ( Zhang et al, 2012 ; Tian et al, 2016 ; Jia et al, 2017 ), the interaction between intracellular molecules of WSS larvae and wheat cannot be underestimated due to these two organisms being in contact and trying to defeat each other. To assess possible effects of larval miRNAs on wheat gene expression and its response to WSS pathogen, target analysis for larval miRNAs was performed against Triticum aestivum coding sequences deposited at ensemble plant database using psRNAtarget tool.…”
Section: Resultsmentioning
confidence: 99%
“…miRNAs from one species may function at interspecies level, targeting genes or genomes of organisms which they have physical contact. Very recently, independent studies have been reported several examples of trans -kingdom delivery of sRNAs from; plant to virion ( Iqbal et al, 2017 ), oomycetes to plant ( Jia et al, 2017 ), plant to nematodes ( Tian et al, 2016 ). Similar to what these studies suggested, miRNAs might also be effective in regulating insect–host interactions at WSS larval stages once larva gets into the stem of the host plant.…”
Section: Introductionmentioning
confidence: 99%
“…Two soybean genotypes ‘KS4607’ and ‘KS4313N’, which are susceptible and resistant to SCN HG type 7, respectively, were used in this study. All seeds were surface sterilized before germination as described by Tian et al [ 74 ]. Healthy germinated seeds were planted into brand new D40 Deepots (Stuewe and Sons, Inc., Corvallis, OR) with sterilized soil and SCN-infested sterilized soil containing approximately 3000 eggs per 100 cm 3 of an HG type 7 H. glycines population.…”
Section: Methodsmentioning
confidence: 99%
“…Three independent biological replicates per treatment were grown under the same conditions as described above, and soybean roots were collected seven days and 35 days post inoculation. Roots were cleaned up with high pressure tap water as standard SCN bioassay procedure as described by Tian et al [ 74 ], and flash frozen in liquid nitrogen and then stored at −80 °C until RNA extraction. Treatments were as follow: KS4607 non-inoculated at 7 dpe (S7C), KS4607 non-inoculated at 35 dpe (S35C), KS4607 SCN inoculated at 7 dpe (S7 N), KS4607 SCN inoculated at 35 dpe (S35 N), KS4313N non-inoculated at 7 dpe (R7C), KS4313N non-inoculated at 35 dpe (R35C), KS4313N SCN inoculated at 7 dpe (R7N), and KS4313N SCN inoculated at 35 dpe (R35N).…”
Section: Methodsmentioning
confidence: 99%
“…miRNA). amiRNA technology has been applied successfully to engineer a wide range of crop species to obtain desirable agronomic traits (Butardo et al, 2011;Toppino et al, 2011;Chi et al, 2014) or enhanced resistance to viruses (Niu et al, 2006;Duan et al, 2008;Kis et al, 2016), fungi (Wang et al, 2016;Zhang et al, 2016b), nematodes (Tian et al, 2016), and insects (Guo et al, 2014). Notably, the amiRNAmediated viral resistance remains effective even at low temperatures (e.g.…”
mentioning
confidence: 99%